The Risk in Living Kidney Donation - Glannon, Walter (Cambridge quarterly of healthcare ethics, 2018)
This article examines two questions. (1) If prospective living kidney donors knew of the lifetime risk of end-stage renal disease (ESRD) in their remaining kidney, then would they be as willing to give it up? and (2) What should transplant organizations and physicians be telling those who express an interest in donating a kidney about risk? Based on the principle that prospective donors must be fully informed of the risk, I raise the issue of a possible obstacle to closing the gap between the availability and need of transplantable kidneys. Some strategies are offered to address this problem.